Goal directed therapy for suspected acute bacterial meningitis in adults and adolescents in sub-Saharan Africa - Wall, Emma C. (PLoS One, 2017)
BACKGROUND: Mortality from acute bacterial meningitis (ABM) in sub-Saharan African adults and adolescents exceeds 50%. We tested if Goal Directed Therapy (GDT) was feasible for adults and adolescents with clinically suspected ABM in Malawi. MATERIALS AND METHODS: Sequential patient cohorts of adults and adolescents with clinically suspected ABM were recruited in the emergency department of a teaching hospital in Malawi using a before/after design. Routine care was monitored in year one (P1). In year two (P2), nurses delivered protocolised GDT (rapid antibiotics, airway support, oxygenation, seizure control and fluid resuscitation) to a second cohort. The primary endpoint was composite mean number of clinical goals attained. Secondary endpoints were individual goals attained and death or disability from proven or probable ABM at day 40. RESULTS: 563 patients with suspected ABM were enrolled in the study; 273 were monitored in P1; 290 patients with suspected ABM received GDT in P2. 61% were male, median age 33 years and 90% were HIV co-infected. ABM was proven or probable in 132 (23%) patients. GDT attained more clinical goals compared to routine care: composite mean number of goals in P1 was 0·55 vs. 1·57 in P2 GDT (p<0·001); Death or disability by day 40 from proven or probable ABM occurred in 29/57 (51%) in P1 and 38/60 (63%) in P2 (p = 0·19). CONCLUSION: Nurse-led GDT in a resource-constrained setting was associated with improved delivery of protocolised care. Outcome was unaffected. TRIAL REGISTRATION: www.isrctn.com ISRCTN96218197